ANALISIS KEPUASAN PENGUNJUNG TERHADAP KUALITAS PELAYANAN DENGAN METODE SERVICE QUALITY (SERVQUAL) DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Rini Purwasih; Aden Aden; Irvana Arofah (Prodi Matematika FMIPA Unirow Tuban, 2022)
Service Quality is an expected advantage by visitors. The purpose of this study is to find out how satisfied visitors are with the service quality at Pasar Modern Bintaro by using the service quality (Servqual) and importance performance analysis (IPA) method. Tangible, responsiveness, reliability, assurance, and emphaty are five dimensions of service quality used to assess visitor satisfaction. The results of the study show that there are gap between expectations and the reality received by visitors with an overall average of -0,72. The highest gap is in the tangible dimension of -0,82 and the lowest gap is in the emphaty dimension of -0,59. Based on Cartesian diagram mapping via importance performance analysis, there are 3 attributes that considered important by visitors but their performance are still low, these attributes include (1) cleanliness and comfort of facilities in the market area, (2) availability of managers in handling complaints quickly, and (3) security when visiting and making transactions.